Assignment of Calibration Information to Deeper Phylogenetic Nodes is More Effective in Obtaining Precise and Accurate Divergence Time Estimates. (January 2014) - Mello, Beatriz; Schrago, Carlos G.
Divergence time estimation has become an essential tool for understanding macroevolutionary events. Molecular dating aims to obtain reliable inferences, which, within a statistical framework, means jointly increasing the accuracy and precision of estimates. Bayesian dating methods exhibit the propriety of a linear relationship between uncertainty and estimated divergence dates. This relationship occurs even if the number of sites approaches infinity and places a limit on the maximum precision of node ages. However, how the placement of calibration information may affect the precision of divergence time estimates remains an open question. In this study, relying on simulated and empirical data, we investigated how the location of calibration within a phylogeny affects the accuracy and precision of time estimates. We found that calibration priors set at median and deep phylogenetic nodes were associated with higher precision values compared to analyses involving calibration at the shallowest node. The results were independent of the tree symmetry. An empirical mammalian dataset produced results that were consistent with those generated by the simulated sequences. Assigning time information to the deeper nodes of a tree is crucial to guarantee the accuracy and precision of divergence times. This finding highlights the importance of the appropriate choice of outgroups in molecular dating.